الآثار السلبية للحروب على نفسية الأطفال وقدراتهم العقلية وسلوكهم - أحمد حمزة (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Our children are our hope, and the future, which we seek to realization, they are the leaders of society, and the superscription of his development, and advancement, so we must keep them and upbringing a good society nurture, and help them, and training them to excess difficulty and problems ,which faces them in their life .the most of social, and education, and supersensible research had averment on the negative role of war on children growth, and their development in all aspects somatic, and mentality , and psychology, and what resulted at them as psychological problems , mentality ,and somatic problems ,which child maybe suffered, and it will be diminish their capability to society consolidation , and what depend on from negative influences on there behavior, which reflected on affright trepidation, and offensive, and ailment , and delinquency, and other things, which can deformed all new generation, and ignore them extremely out of civilization . أطفالنا هم آمالنا في مستقبل نسعى جاهدين لتحقيقه, فهم قادة المجتمع, و عنوان تطوره وتقدمه لذلك يتوجب علينا رعايتهم، والمحافظة عليهم، وتنشئتهم التنشئة الصالحة السليمة وتقديم العون لهم وتدريبهم على تجاوز المحن والصعاب التي قد يواجهونها في حياتهم ، وقد أكّدت معظم الدراسات الاجتماعية و التربوية ، والنفسية على الدور السلبي للحروب على نمو الأطفال ، وتطورهم في مختلف النواحي الجسدية والعقلية و النفسية ، وما ينجم عن ذلك من اضطرابات نفسية وعقلية وجسدية قد يعاني منها الأطفال وقد تحد من قدراتهم على الاندماج الاجتماعي وما يترتب على ذلك من آثار سلبية على سلوكهم يتجلى ذلك في الخوف والعدوانية و القلق والإهمال، وغيرها من العوامل التي قد تؤدي إلى تشويه جيل كامل وأبعاده عن الحضارة نهائياً .